2008
DOI: 10.1016/j.visres.2008.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of eccentricity and retinal illuminance on the illusory motion seen in a stationary luminance gradient

Abstract: Kitaoka recently reported a novel illusion named the Rotating Snakes [Kitaoka, A., & Ashida, H. (2003). Phenomenal characteristics of the peripheral drift illusion. Vision, 15, 261-262], in which a stationary pattern appears to rotate constantly. In the first experiment, we attempted to quantify the anecdote that this illusion is better perceived in the periphery. The stimulus was a ring composed of stepwise luminance patterns and was presented in the left visual field. With increasing eccentricity up to 10-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 43 publications
6
50
1
Order By: Relevance
“…While it is unrealistic to assume biased spatial derivative filters, the temporal derivative filters are causal and more likely have an imbalance of positive and negative lobes of their impulse response, which would introduce a bias. The assumption that decrease of contrast is overestimated compared to increase of contrast (see Figure 9 in Murakami et al, 2006), which is consistent with psychophysically derived temporal impulse responses (Burr & Morrone, 1993; Hisakata & Murakami, 2008), explains the observed illusory motion.…”
Section: Discussionsupporting
confidence: 81%
“…While it is unrealistic to assume biased spatial derivative filters, the temporal derivative filters are causal and more likely have an imbalance of positive and negative lobes of their impulse response, which would introduce a bias. The assumption that decrease of contrast is overestimated compared to increase of contrast (see Figure 9 in Murakami et al, 2006), which is consistent with psychophysically derived temporal impulse responses (Burr & Morrone, 1993; Hisakata & Murakami, 2008), explains the observed illusory motion.…”
Section: Discussionsupporting
confidence: 81%
“…They suggested that the direction of the perceived motion is from black, to dark gray, white, and light gray-a luminance profile that, for example, produced the "Rotating Snakes" (Kitaoka, 2003) illusion. Studies have quantitatively confirmed that the motion in this illusion appears more in peripheral vision (Beer, Heckel, & Greenlee, 2008;Hisakata & Murakami, 2008) and that the illusion is weaker for senior observers (Billino, Hamburger, & Gegenfurtner, 2009). One characteristic common to both the FW illusion and the modified FW illusion is that steady fixation weakens the illusory motion, and eventually halts it within several seconds.…”
mentioning
confidence: 76%
“…Some illusions, such as the popular "rotating snake" illusion, are more effective in the peripheral visual field (Hisakata and Murakami, 2008), and some can be altered by eccentricity (Murakami and Shimojo, 1993). Interestingly, illusory percepts of visual flashes can be induced by sounds, and the illusion is stronger in the peripheral visual field (Shams et al, 2002).…”
Section: The Functions Of the Far Peripheral Visual Fieldmentioning
confidence: 99%